Triglyceride glucose-waist circumference as a useful predictor for diabetes mellitus: a secondary retrospective analysis utilizing a Japanese cohort study - Yawei Li; Linlin Shan; Qiong Wen; Changchun Cao; Meiling Huang; Chunxia Zhang; Xiaoping Li; Kun Wang; Tianlun Zhou; Fubing Zha; Yulong Wang (BMC Endocrine Disorders)
Abstract Background and objective While the connection between the Triglyceride glucose-waist circumference (TyG-WC) index and the risk of diabetes remains understudied, this particular research delves into the potential predictive value of the TyG-WC index within a significant Japanese population. Methods This retrospective cohort study encompassed a comprehensive analysis of 15,413 Japanese adults, all of whom were diabetes-free at the outset of the study period from 2004 to 2015. Comprehensive medical records were obtained for all participants who underwent physical examinations. The study employed Cox proportional-hazards regression, smooth curve fitting, various sensitivity, and subgroup analyses to explore the association between TyG-WC and the development of diabetes. Furthermore, a Receiver Operating Characteristic (ROC) curve was created to detect the predictive capability of TyG-WC for diabetes risk. Results After a maximum of 13.0 years of follow-up, 358 people finally developed diabetes. Upon adjusting for covariates, the result showed TyG-WC was positively and independently associated with incident Diabetes Mellitus (DM) (Hazard Ratio (HR): 1.004, 95%C: 1.001–1.006). Furthermore, ROC curve analysis demonstrated that TyG-WC outperformed both the triglycerides-glucose index and triglyceride glucose-body mass index in predicting the onset of diabetes. Conclusion High levels of TyG-WC are autonomously linked to a heightened risk of diabetes in the Japanese demographic, indicating its potential as a dependable predictive indicator for diabetes mellitus in individuals at elevated risk.